Developing Higher Order Thinking Skills Test Instruments for English Speaking Classes: Sing a Song Material - Multazam Abubakar; Nurfatwa Putri Husain; Mardiana Mardiana (Eduvelop: Journal of English Education and Development, 2022)
This study aims at creating HOTS items for the "Sing a Song" material, establishing their level of validity, and determining their dependability for tenth-grade students of MA Madani Alauddin Pao-Pao. The design of this research is research and development (R&D). The improvement version this is used refers back to the Plomp version which includes five levels of development, namely Preliminary investigation, Design, Realization/Construction, Test, Evaluation and Revision (Test, Evaluation and Revition), and Implementation (Implementation). The subjects in this study are students at class X MIA 2 in MA Madani Alauddin Pao-Pao. The instruments used in data collection were validation sheets and HOTS items. Based on the findings of the study, it obtains that the extent of validity of the HOTS gadgets changed into 3.7 that is withinside the very legitimate category, the reliability of the HOTS gadgets is 0.81 suggests in superb category, the issue degree of the HOTS gadgets is 0.60 suggests withinside the medium category. The implications of developing HOTS items can train and encourage students to do high-level reasoning so that they are not fixated on the pattern of answers that result from memorization without understanding the concept of knowledge, and can make students think critically while working on the test in the "Sing a Song "Material so that answers can be produced based on in-depth reasoning.